The Incidence and Effectiveness of Prior Actions in IMF-supported Programs - Ramakrishnan, Uma (IMF Working Papers; Working Paper ;, 2006)
Prior actions are measures that need to be implemented prior to Board approval of an IMFsupported program. This paper examines whether such prior actions can signal a willingness to implement reforms, especially when the member's track record is weak. We find some support for this signaling role, particularly for programs supported by the General Resources Account (GRA). Controlling for the member's previous track record, prior actions are associated with greater compliance with other structural conditions, suggesting their possible use as a screening device. Moreover, prior actions set at program approval serve as a useful screening device and strengthen the macroeconomic targets set out in the IMF-supported program. The results also reveal a demonstrable screening effect on growth over the medium term, since the growth impact of the ratio of prior actions at the outset versus the rest of the program is significantly positive while the total number of prior actions is not statistically significant.